The Role of Management Information Systems in Hospital - Meiryani; Siagian, Pariang; Damanik, Elina Magdalena; Djuanda, Gustian (International Journal of Psychosocial Rehabilitation, 2020)
Hospital management information system aims to provide understanding and increase the capabilities of hospital human resources, academics, students, and the general public about integrated hospital management information systems to handle various things ranging from diagnostic services and actions for patients, medical records, pharmacies, pharmaceutical warehouse, billing, personnel, employee payroll, accounting process until control by hospital management.